Conflict prevention and peace management - Chatterji, Manas; Chatterji, Madhumita; Sharma, Kshitiz (Contributions to conflict management, peace economics and development, 2025)
This volume contains some selected papers from the "International Conference on Peace Economics, Peace Science and Development", held at the Mahatma Gandhi Center for Conflict Prevention and Management in Bangalore, India on July 11 to 13, 2024. The chapters cover the topics of social conflict, socioeconomic inequalities, ethnic animosity, and natural resources accessibility, and more in the Indian Subcontinent and Africa. The authors demonstrate how to use theories and methodologies from Peace Economics and Peace Science as well as cultural spirituality, nature therapy, and art forms to address issues to find more sustainable and productive ways for international and regional communities to cohabitate and collaborate harmoniously. Conflict Prevention and Peace Management appeals to researchers, policymakers and those interested in Conflict Management and Peace Studies, along with politics, sociology, economics, and psychology.